A virtual orchestra to qualify the acoustics of historical opera houses. Issue 3 (September 2020) - D'Orazio, Dario; Fratoni, Giulia; Rovigatti, Anna; Garai, Massimo
Italian Historical Opera Houses are private or public spaces built around a cavea, with tiers of boxes on the surrounding walls. At the early age – from 16th to 18th century – boxes were private properties of the richest class, typically the financial responsible of the whole building. The stalls hosted the middle class, that gradually increased its social position and for this reason the wooden seats were progressively replaced by chairs. The gallery was reserved to lower classes. Does this social division correspond to a different acoustic comfort? The present work tries to answer this question using subjective preference models provided by scholars. With this aim, the room criteria defined by different authors and in distinct times are lined up with the ISO 3382 standards and analysed depending on the acoustic peculiarities of an Italian Historical Opera House selected as case study. Calibrated impulse responses were handled through the numerical simulations of a whole orchestra of virtual sound sources in the pit.